A Thin Film Black Phosphorus Light-Emitting Diode - Wang, Junjia; Rousseau, Adrien; Yang, Mei; Low, Tony; Francoeur, Sebastien; Kena-Cohen, Stephane (2020 Conference on Lasers and Electro-Optics (CLEO), 2020)
We demonstrate a black phosphorus light-emitting diode based on a black phosphorus/molybdenum disulfide heterostructure. The device shows an electroluminescence maximum at a wavelength of 3.68 μm with an internal quantum efficiency of ∼1%.